Associação entre graus de disfunção erétil e fatores de risco cardiovascular em pacientes de hospital universitário - Maia, Aline Cristine Salum Fernandes (2016)
Erectile dysfunction (ED) is defined as the persistent inability to achieve or maintain an erection adequate for satisfactory sexual activity. Despite non-lethal, ED can negatively affect on the life quality of these patients. Objective: The purpose of the present study was to assess cardiovascular risk factors in patients with ED considering: 1- sociodemographic characterization of patients with ED; 2- identification of cardiovascular risk factors in these patients and, 3- association between degrees of ED and cardiovascular risk factors. Patients and Method: A total of 56 patients with ED with and without cardiovascular risk factors, were prospectively studied in an outpatient of Urology in a school hospital from September 2013 to December 2014. The ED was classified as mild, moderate and severe using the International Index of Erectile Function. Sociodemographic (age, marital status, presence and number of children, and geographic origin) and clinical data related to cardiovascular risk factors (systemic arterial hypertension (SAH), diabetes, alcohol drinking, overweight and smoking) were obtained using a questionnaire. Cross- frequency tables were used to verify association among degrees of ED and sociodemographic and clinical variables. Results: Mean age of patients with ED was 57.4 ± 8.4 years. Most of them was married (82.1%); 85.7% had children; 73.3% had incomplete fundamental education. The geographic origin predominant was São José do Rio Preto region (62.5%). More frequent ED degree was severe (75%), followed by moderate (17.9%), and mild (7.1%). SAH was the cardiovascular risk factor most common (53.6%). The comparison among mean age and mean BMI according to ED degree did not show statistically significant difference (p = 0.25 and p = 0.37, respectively). There was not a significant difference between number of children and degrees of ED (p = 0.99). The association between degrees of ED and cardiovascular risk factors (SAH, diabetes, smoking, and alcohol drinking) was not significant. Conclusions: There was predominance of patients with ED in the sixty decade of life, most married, with low educational level. SAH was the most frequent cardiovascular risk factor followed by diabetes, overweight, alcohol drinking, and smoking. Most hypertensive patients exhibited severe ED. The majority of patients with severe ED can be related to the high and concurrent frequency of cardiovascular risk factors. There was not a significant association between ED and cardiovascular risk factors.